Disorder in the Court : Morality, Myth, and the Insanity Defense - Alden, Andrea L., 1977- (Book collections on Project MUSE., 2018)
"The insanity defense is considered one of the most controversial, most misunderstood, and least straightforward subjects in the American legal system. Disorder in the Court: Morality, Myth, and the Insanity Defense traces the US legal standards for the insanity defense as they have evolved from 1843, when they were first codified in England, to 1984, when the US government attempted to revise them through the Insanity Defense Reform Act. Throughout this period "insanity" existed primarily as a legal term rather than a medical one; yet the testimony of psychiatric experts is required in cases in which an insanity defense is raised"--